Urgensi Pengaturan Artificial Intelligence pada Sektor Bisnis Daring di Indonesia - Shabrina Fadiah Ghazmi (CV Rewang Rencang, 2021)
Technological advances provide convenience to humans in their activities. One of them is Artificial Intelligence (AI) which is used by various sectors, including the online business sector. However, there are negative impacts of the use of AI, such as the emergence of AI actions that violate ethics, the rule of law, or cause harm to others who must be held accountable. The unrecognized AI as a legal subject in Indonesia, both civilly and criminally, can create other problems. The results showed that accountability for AI actions can be the responsibility of the person or legal entity on it based on the doctrine of vicarious liability. The establishment of specific regulations governing AI is also needed as a preventive measure.